Factors influencing investment activity with financial constraints / Najmi Hasif Anuar - Anuar, Najmi Hasif (2021)
The lack of study relating to a firm investment activity based on their financial constraint is becoming a growing concern. The problem of not knowing the potential growth of the company and the risk associated with the growth cannot be simply solved by just referring to the firm financial statement without better understanding on the relationship between the financial constraints and the investment behaviour of the firm. This research is based on a balanced panel dataset of Malaysia listed firm in the Main Market Construction Sector over the period 2011-2016. The regression result shows that the level of debt significantly impacts a firm investment.